Indigenous Knowledge of Banyuwangi in the Blambangan Museum Collections - Rizki Nurislaminingsih; Heriyanto Heriyanto; Hervina Nurullita; Nuning Kurniasih (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2026)
Background: Banyuwangi is widely recognized for its rich cultural heritage and growing cultural tourism sector. Museums play an important role in preserving and disseminating cultural information, including indigenous knowledge embedded within cultural artifacts. The Blambangan Museum houses a variety of historical collections representing the cultural heritage of Banyuwangi and the Osing community. These collections provide an opportunity to explore indigenous knowledge preserved through material culture.Objective: This study aims to identify and analyze forms of indigenous knowledge represented in the collections of the Blambangan Museum, BanyuwangiMethods: This study employed a qualitative approach using a museum studies perspective. Data were collected through direct observation of museum collections, analysis of artifact labels, and examination of museum information boards. The analyzed collections included pottery, jewelry, wayang, batik, woven bamboo products, traditional household objects, ritual artifacts, traditional weapons, and information related to the Macan Putih Temple. Data were analyzed through thematic categorization of indigenous knowledge represented in the collections, while relevant literature was used to support interpretation of the findings.Results: The findings reveal five forms of indigenous knowledge represented in the museum collections: (1) traditional craftsmanship and production knowledge, reflected in pottery, jewelry, wayang, batik, and weaving traditions; (2) environmental and natural resource knowledge, demonstrated through the use of natural materials and local resources; (3) social and cultural knowledge, represented in traditional games, household objects, and cultural practices; (4) spiritual and ritual knowledge, reflected in ceremonial objects, ritual traditions, and performance arts; and (5) traditional technological and architectural knowledge, represented in metalworking traditions, traditional tools, and temple-related heritage.Conclusion: The collections of the Blambangan Museum function not only as cultural artifacts but also as repositories of indigenous knowledge preserved through material culture. The findings highlight the role of museums as information institutions that support the preservation, interpretation, and dissemination of local knowledge. Understanding museum collections from an indigenous knowledge perspective may enrich cultural interpretation, strengthen local identity, and support cultural heritage preservation initiatives.